FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ASAM URAT PADA LANSIA (45 – 70 TAHUN) - Ridhyalla Afnuhazi (Universitas Fort De Kock, 2019)
Indonesian is the 4th largest country in the world whose in habitants suffer from gout. In Indonesian, it is estimated that uric acid occur in 840 people every 100,000 people. Disease of gout is one of the degenerative disease. One of the signs of the disease gout is the increase in the levels of uric acid in the blood (hiperurisemia). Factors related to the incidence of hiperurisemia is sex, IMT, intake carbohydrate sand intake purin. Purin intake is a risk factor most strongly associated with the incidence of hiperurisemia. This study used a cross-sectional research design cross method i.e. research to study the dynamics of the correlation between two variables. Research carried out in the Puskesmas Kebun Sikolos in August 2016. The population in this study amounts to 100 people. Sampling techniques in